Investigation of the Simultaneous Effect of Electrolyte Additives and α-PbO2 Intermediate Layer on the Electrodeposition of Ti/β-PbO2 Electrode - Hadi Sharifidarabad; Alireza Zakeri; Mandana Adeli (Iranian Journal of Materials Science and Engineering, 2024)
The sensitivity of lead dioxide coating properties to the deposition conditions and electrolyte composition has allowed the preparation of coatings with different properties for different applications. In this study, the effects of electrolyte additives on the electrodeposition process were investigated using electrochemical measurements such as cyclic voltammetry, chronoamperometry and electrochemical impedance spectroscopy. The results showed that the presence of fluoride ions significantly reduce the possibility of TiO2 formation. The addition of copper ions not only prevents lead loss at the cathode, but also leads to the formation of copper oxide on the surface at initial stages, which hinders nucleation of PbO2. The presence of sodium dodecyl sulfate (SDS) also interferes with the nucleation process as it occupies active nucleation sites. The α-PbO2 interlayer prevents copper oxidation and solves the problem of lead dioxide nucleation. Finally, it was found that the simultaneous use of all additives together with the α-PbO2 interlayer has a positive effect on the coating process.